Diversification of the Renewable Furanic Platform via 5‐(Chloromethyl)furfural‐Based Carbon Nucleophiles. Issue 1 (5th October 2020) - Miao, Haoqian; Shevchenko, Nikolay; Otsuki, Andrew L.; Mascal, Mark
Abstract: Biobased 5‐(chloromethyl)furoate and 5‐methylfuroate esters can be deprotonated to function as furylogous lithium enolates, and the former can also undergo zinc insertion to access Reformatsky‐type chemistry. Carbon nucleophilicity represents hitherto little‐explored reactivity in these key carbohydrate‐derived platform molecules, expanding their synthetic utility and potentially opening up new sustainable product markets (e. g., in epoxy resins or biobased dyes). Abstract : Umpolung ! Native charge affinity patterns (electrophilic C in blue and nucleophilic C in red) are shown for HMF and CMF . The synthetic versatility of biomass‐derived CMF is further expanded in this work by rendering the methylene carbon nucleophilic, either by deprotonation or metal insertion.